2005
DOI: 10.1136/adc.2004.052720
|View full text |Cite
|
Sign up to set email alerts
|

DT5aP-Hib-IPV and MCC vaccines: preterm infants' response to accelerated immunisation

Abstract: Aims: To describe the immune response of preterm infants to combined diphtheria/tetanus/5 component acellular pertussis-Haemophilus influenzae type b inactivated polio vaccine (DT5aP-Hib-IPV) and meningococcal serogroup C conjugate vaccine (MCC) under accelerated schedule. To compare results with term infants immunised with DT5aP-Hib-IPV and with historical data from preterm infants immunised with a DT3 component aP-Hib vaccine. Methods: Prospective observational study in preterm infants born at ,32 weeks gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…All preterm infants achieved a level ≥1:8 for serotypes I, II and III-there was no statistically significant difference between the preterm and the 60 term control infants. 24 Kitchin et al reported that 100% of healthy infants immunized with either IPV or OPV on a 2, 3 and 4 month schedule responded to polio types 1 and 2 with ≥97.9% protected against type 3. 14 D'Angio reported on 16 extremely premature infants (mean gestational age 25.9 weeks) given eIPV at 2 months followed by OPV at 4 months: equivalent proportions of preterm and term infants were protected (using a neutralizing antibody titre ≥1:8) against serotype I (85 and 80%) and serotype II (100% each): fewer preterm infants were protected against serotype III (31% and 90%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All preterm infants achieved a level ≥1:8 for serotypes I, II and III-there was no statistically significant difference between the preterm and the 60 term control infants. 24 Kitchin et al reported that 100% of healthy infants immunized with either IPV or OPV on a 2, 3 and 4 month schedule responded to polio types 1 and 2 with ≥97.9% protected against type 3. 14 D'Angio reported on 16 extremely premature infants (mean gestational age 25.9 weeks) given eIPV at 2 months followed by OPV at 4 months: equivalent proportions of preterm and term infants were protected (using a neutralizing antibody titre ≥1:8) against serotype I (85 and 80%) and serotype II (100% each): fewer preterm infants were protected against serotype III (31% and 90%).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in age specific disease incidence following PnC vaccine programs support use of this figure as the appropriate immune correlate measure. 1,2 Ruggeberg et al immunized 68 pre-term infants (median gestational age 30 weeks [23][24][25][26][27][28][29][30][31][32][33][34][35][36]) with a 7 valent pneumococcal conjugate vaccine (Prevenar) using a 2, 3 and 4 month schedule. Serological assessment at 4 weeks after the 3 rd dose showed that protective GMCs had been induced for 6 out of the 7 serotypes in the vaccine-for type 6B only 41% of subjects had acquired a level of ≥0.35 µg/mL [for all the other serotypes ≥81% were protected].…”
mentioning
confidence: 99%
“…The safety and immunogenicity of DTaP 5 -IPV-Hib using 3-dose primary vaccination schedules have previously been demonstrated in clinical studies in infants (1)(2)(3)(4)(5)(6)(7)(8) and toddlers (4,(9)(10)(11). This is the first study to have evaluated the 3-, 5-, and 12-month schedule employed in some countries, particularly in Europe, and to have compared the safety and immunogenicity of …”
mentioning
confidence: 99%
“…However, HBV causes the same response in premature children as in term infants from 1 month of age regardless of GA and birth weight. Various schemes have been tested in this respect, including scheme 2-4-6 months, which produced the results comparable with the results in term infants [15,[31][32][33][34]. The given data served as the basis for formulation of vaccination tactics for premature infants.…”
Section: Immunogenicity and Reactogenicity In Premature Infantsmentioning
confidence: 90%
“…However, the authors emphasize that the vaccination has protective effect for this group, too [37]. It appears that the shortened primary immunization does not produce sufficient results in small premature infants, while almost all children, including premature infants with GA ≤29 weeks, developed protective antibody levels after 3 administrations of a CRM 197 -conjugate vaccine with at 2, 4 and 6 months of age [33]. Similar results were obtained at administration of a hexa vaccine (scheme 2-4-6, 18-24 months).…”
Section: Vaccine Against the Infection Caused By Haemophilus Influenzmentioning
confidence: 99%